Use of electronic medical records in oncology outcomes research - Gena Kanas; Libby Morimoto; Fionna Mowat; et al (Dove Medical Press, 2010)
Gena Kanas1, Libby Morimoto1, Fionna Mowat1, Cynthia O’Malley2, Jon Fryzek3, Robert Nordyke21Exponent, Inc., Menlo Park, CA, USA; 2Amgen, Inc., Thousand Oaks, CA, USA; 3MedImmune, Gaithersburg, MD, USAAbstract: Oncology outcomes research could benefit from the use of an oncology-specific electronic medical record (EMR) network. The benefits and challenges of using EMR in general health research have been investigated; however, the utility of EMR for oncology outcomes research has not been explored. Compared to current available oncology databases and registries, an oncology-specific EMR could provide comprehensive and accurate information on clinical diagnoses, personal and medical histories, planned and actual treatment regimens, and post-treatment outcomes, to address research questions from patients, policy makers, the pharmaceutical industry, and clinicians/researchers. Specific challenges related to structural (eg, interoperability, data format/entry), clinical (eg, maintenance and continuity of records, variety of coding schemes), and research-related (eg, missing data, generalizability, privacy) issues must be addressed when building an oncology-specific EMR system. Researchers should engage with medical professional groups to guide development of EMR systems that would ultimately help improve the quality of cancer care through oncology outcomes research.Keywords: medical informatics, health care, policy, outcomes